TEACHERS EXPERIENCES IN RELATION TO ONLINE TEACHING/LEARNING DURING THE COVID-19 PANDEMIC (Heritage, 2022)
The current Covid-19 pandemic has completely changed the life of modern society and many of its segments. Undoubtedly, it influenced the entire education and the format of teaching so the online teaching and learning have become the most valuable tools in the emergency situation we are currently in. In this regard, the paper emphasizes, first of all, the explanation of online teaching and learning, the review of distance learning during the pandemic, as well as a brief overview of previous domestic and foreign researches on this topic. In order to research how the teachers coped in this situation, what are their experiences with online teaching, a research was conducted with foreign language teachers on the territory of Serbia. Therefore, in the second part of the paper, research methods are presented, as well as the results of a survey and interviews with foreign language teachers. The results showed that as the benefits of online teaching, teachers singled out the ease of preparation of classes, students' interest in teaching, increased quality of teaching materials, the possibility of faster and easier access to materials. On the other hand, the shortcomings of this type of teaching include insufficiently developed digital literacy of teachers, student workload, lack of time, technical equipment, poor internet connection and inability to control student work.
Keywords: online teaching, teachers, students, foreign languages, education, Covid-19